Theater design - Izenour, George; Knudsen, Vern O.; Newman, Robert B.; Nagler, Alois M. (New York : McGraw Hill Education, 1977)
The work that is this book began 10 years ago as monograph on the design of the multiple-use theater, in which a dozen or so buildings selected from consulting collaborations with colleagues Vern O. Knudsen and Robert B. Newman were to have been discussed, analyzed and compared.
List of illustrations -- Foreword -- Acknowledgments -- Preface -- 1. Introduction : vision, hearing, and seating -- 2. Historical development of theater design -- 3. Chronological and graphical development of theater design, 300 B.C. to 1975 -- 4. Building codes -- 5. Contemporary multiple-use theater design -- 6. Programming and design : collaboration of client, architect, and consultants -- 7. Multiple-use theater design practice of George C. Izenour -- 8. Acoustical design of multiple-use auditoria / Vern O. Knudsen -- 9. Adjustable acoustics for the multiple-use auditorium / R.B. Newman -- 10. Theater engineering systems design for the multiple-use auditorium and stage -- 11. The building budget: financing and coat analysis -- 12. Comparisons and recapitulation -- Appendix 1: Chronological chart of ancient discoveries, philosophers, inventors, engineers, inventions, architects,musicians, dramatists, etc. -- Appendix 2: Chronological chart of modern scientific discoveries, scientists, inventions, engineers, inventors, architectects,musicians, dramatists,etc. -- Appendix 3: Elementary considerations of some principles in the construction of buildings designed to accomodate spectators and auditors -- Appendix 4: Architectural acoustics -- Appendix 5: A director views the stage -- Appendix 6: The grosses Schauspielhaus in Berlin -- Appendix 7: Acoustical design in the hill memorial auditorium, University of Michigan -- Bibliography -- Name Index -- Theater index -- Subject index.
Includes bibliographical references and index.
Keywords: THEATER ARCHITECTURE